2012
DOI: 10.1021/ja303117z
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Effects of Terminal Groups and Solvents on Helical Folding of o-Phenylene Oligomers

Abstract: Although o-phenylene oligomers (OP(n)R) made of dimethoxyphenylene units are thought to be intrinsically dynamic due to π-electronic repulsion, we show that they fold into a regular helical geometry in CH(3)CN when they carry terminal groups such as CH(3), CH(2)OH, Br, CO(2)Bn, and NO(2). We evaluated their helical inversion kinetics via optical resolution of long-chain oligomers (e.g. 16- and 24-mers) by chiral HPLC. OP(24)Br at 298 K shows a half-life for the optical activity of 5.5 h in CH(3)OH/water (7/3 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
100
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(106 citation statements)
references
References 32 publications
4
100
2
Order By: Relevance
“…Supporting Information (see footnote on the first page of this article): Experimental details, characterization data, and copies of the 1 H NMR and 13 C NMR spectra of all key intermediates and final products.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting Information (see footnote on the first page of this article): Experimental details, characterization data, and copies of the 1 H NMR and 13 C NMR spectra of all key intermediates and final products.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Due to their heavily angled aromatic connection, oligomeric o-phenylenes are able to adopt a closely packed helical conformation featuring axial chirality. Oligomeric and polymeric o-phenylenes, consisting of multiple phenylene units linked together at their ortho-positions, are an emerging class of such helical molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Connections of aromatics through non-a or non-para positions for five-and six-membered rings, respectively, impart unique topologies onto the secondary structures of p-conjugated wires through heavily angled aromatic connections. [1][2][3][4][5][6][7][8] The conformational behaviors of o-phenylenes, in particular, have been extensively studied in regard to their dynamic nature, redox response, and effect of substituents and end-groups. [2][3][4][5] However, there are only a few examples of o-arylene analogues composed of more compact five-membered heteroaromatics despite their versatility in p-conjugated molecular wires with excellent electric and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The conformational behaviors of o-phenylenes, in particular, have been extensively studied in regard to their dynamic nature, redox response, and effect of substituents and end-groups. [2][3][4][5] However, there are only a few examples of o-arylene analogues composed of more compact five-membered heteroaromatics despite their versatility in p-conjugated molecular wires with excellent electric and optical properties. [6][7][8] Recently, Fallon et al reported the synthesis of b-oligofurans and their conformational preferences.…”
Section: Introductionmentioning
confidence: 99%